Review of wireless body area networks: protocols, technologies, and applications - Al-Sofi, Soleen Jaladet; Atroshey, Salih Mustafa S.; Ali, Ismail Amin (Bulletin of Electrical Engineering and Informatics, 2023)
Nowadays, technology plays a vital part in our daily lives. Especially in medicine, such as consultations, examination, and operation, these processes are necessary and must be utilized accordingly. Medical checkups are required to ensure the patient’s wellbeing. However, many people suffer from severe health conditions and are not always able to leave the house for examination. They are also not aware of potential risks within their body and therefore, don’t feel the need to be examined. With the rise of new technological advantages, new solutions are being presented to tackle those issues. In the field of wireless sensor networks (WSNs), the wireless body area network (WBAN), alongside with its features and functionalities, can be regarded as one of the potential innovations for medicine, military, sport, and entertainment. With its tiny sensors, as well as with its plethora of applications, the WBAN is an excellent choice for remote medical surveillance and treatment. Furthermore, various routing protocols can provide proper solutions, depending on the application needs. However, challenges, such as energy efficiency, and security. are being further developed to improve the needs of its demands. This review is an overview of WBAN technologies, protocols, applications and potential challenges.